A discursive approach to disagreements expressed by Chinese spokespersons during press conferences. (October 2020) - Mao, Yansheng; Zhao, Xin
Abstract: Most previous research on (im)politeness in Chinese has not centered on disagreement in unequal-status situations. This paper examines the discursive processes which are involved in the construction and negotiation of disagreement expressed by government spokespersons when they are confronted with a diverse range of journalistic questions. Drawing on 40 h of video-recorded press conferences released by the Ministry of Foreign Affairs of the People's Republic of China, we will argue that spokespersons often respond to questions by employing a number of disagreement strategies (giving opposing opinions, making negative comments, raising rhetorical questions, taking a personal stance, making an ironic statement and providing facts). Through the use of such forms of disagreement behavior, the spokesperson not only manages the (potential) face-threats that are triggered by the questions, but also positions the government as a 'moral actor' in the media. A close look at these conversations between spokespersons and journalists reveal that cultural and socio-political issues could provide possible reasons for these usages of disagreement expressed in Chinese press conferences.